The influence of age, gender, frequency of teaching and starting competency level on the acquisition of water competencies in relation to drowning prevention among beginners - Junge, M.; Stallman, R. K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
A variety of factors affect the learning of beginning water competencies. The aims of this study were to examine the effects of age, gender, starting level and teaching frequency on learning beginning water competencies. One hundred sixteen, five and six-year-olds participated. Eighteen hours of instruction were conducted, once or twice per week, about half in each group and equal numbers by gender. The teaching progression of 25 skills served as the assessment tool. Starting level was assessed on the first day of instruction. Final achievement was defined as the total number of items mastered (0-25). Progress was defined as the number of items mastered minus the number indicated by the starting level, i.e. "new" items mastered. Goodman-Kruskal`s gamma coefficient was used to correlate starting level, age and teaching frequency with both final achievement and progress. The influence of gender was calculated by Cramer`s coefficient. Almost no relationship was found between gender and either final achievement or progress. The Cramer correlation coefficients were 0.09 and 0.04, respectively. Teaching frequency related poorly (gamma = 0.20 and 0.11, respectively). Age related moderately to achievement and progress with gamma coefficients of 0.38 and 0.29, respectively. Starting skill level related well to both achievement and progress with gamma coefficients of 0.87 and 0.75, respectively. This supports the conventional wisdom that every effort should be made to increase the level of readiness before formal teaching commences.